2015
DOI: 10.3390/buildings5030860
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Complex Healthcare Features on Construction Waste Generation

Abstract: Over recent years, the British government has been investing billions of pounds in new and refurbished healthcare building projects. With the rapid growth in investment in healthcare infrastructure throughout the United Kingdom, a number of sustainability issues have been created, including construction waste generation. There is growing consensus in the literature that healthcare buildings are "complex", due to their unique functional and operational features, and are thus more prone to generating larger amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The root cause of these problems is the absence of effective communication and cooperation among the involved parties [99]. Ineffective communication, inadequate scope definition, and the diverse technical backgrounds of stakeholders are the major problems in the pre-design phase of a project, which makes a complex decision environment for the design team [70,100]. Nevertheless, as advocated by a study carried out by the researchers, the best-practice measures for CW minimisation include the "collaboration of stakeholders" [14].…”
Section: Factors Affecting Design Stage Waste Minimisation Practices:...mentioning
confidence: 99%
“…The root cause of these problems is the absence of effective communication and cooperation among the involved parties [99]. Ineffective communication, inadequate scope definition, and the diverse technical backgrounds of stakeholders are the major problems in the pre-design phase of a project, which makes a complex decision environment for the design team [70,100]. Nevertheless, as advocated by a study carried out by the researchers, the best-practice measures for CW minimisation include the "collaboration of stakeholders" [14].…”
Section: Factors Affecting Design Stage Waste Minimisation Practices:...mentioning
confidence: 99%
“…Bekr [50] indicated that the most important causes of materials wastage on construction sites were design changes, rework, poor documents, improper and inadequate of materials storage, poor waste management strategy, lack of skilled workers, bad site conditions, damaged material during transportation, mistakes in quantity estimation and over allowance, and theft and vandalism. Domingo [51] conducted research on the generation of construction waste factors in construction. The findings revealed that incorrect information on drawings, incomplete briefing, complicated designs, non-standard designs, and poor coordination in the building construction lifecycle were the construction waste causes.…”
Section: Construction Materials Waste Generation Factorsmentioning
confidence: 99%
“…[Bekr., (2014)] indicated that the main causes of waste materials on construction sites were changes in design, rework, poor documentation, improper and inadequate storage of materials, poor waste management strategy, lack of skilled workers, poor site conditions, damaged material during transportation, mistakes in quantity estimation and over allowance estimation, and theft and vandalism. [Domingo, (2015)] researched on constructing waste generation factors. The findings revealed that the causes of construction waste were incorrect drawings, imperfect update, complex designs, non-standard designs, and poor management in the building lifecycle.…”
Section: Waste Generation Factorsmentioning
confidence: 99%